2013
DOI: 10.1371/journal.pgen.1003522
|View full text |Cite
|
Sign up to set email alerts
|

ttm-1 Encodes CDF Transporters That Excrete Zinc from Intestinal Cells of C. elegans and Act in a Parallel Negative Feedback Circuit That Promotes Homeostasis

Abstract: Zinc is an essential metal involved in a wide range of biological processes, and aberrant zinc metabolism is implicated in human diseases. The gastrointestinal tract of animals is a critical site of zinc metabolism that is responsible for dietary zinc uptake and distribution to the body. However, the role of the gastrointestinal tract in zinc excretion remains unclear. Zinc transporters are key regulators of zinc metabolism that mediate the movement of zinc ions across membranes. Here, we identified a comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 45 publications
3
55
0
Order By: Relevance
“…elegans , including the zinc transporter genes cdf-2 and ttm-1b [13,14]. To identify genes that mediate this response, we screened for mutant animals that displayed abnormal regulation of cdf-2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…elegans , including the zinc transporter genes cdf-2 and ttm-1b [13,14]. To identify genes that mediate this response, we screened for mutant animals that displayed abnormal regulation of cdf-2 .…”
Section: Resultsmentioning
confidence: 99%
“…elegans contains 14 cation diffusion facilitator (CDF) genes that encode transporters for zinc and possibly other metal ions. The CDF genes cdf-2 and ttm-1b are transcriptionally up-regulated in intestinal cells by high dietary zinc, and these transporters promote zinc storage and excretion [14,19]. Transcriptional activation of these genes is mediated by the high zinc activation (HZA) element, a DNA enhancer [15].…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory function similar to CDF1 is conducted by SUR-7 (no vertebrate ZnT homologs), which is probably localized to the ER. In homeostatic control, CDF2 (a ZnT2 homolog) or TTM-1 (no vertebrate ZnT homologs) also plays a crucial role by transporting zinc into gut granules (lysosome-related organelles) or excreting zinc from the apical plasma membrane in intestinal cells, respectively (348,349).…”
Section: Role Of Zinc Transporters In Zinc Homeostasis and Metabolismmentioning
confidence: 99%
“…Roh et al showed that TTM-1B is induced by high dietary Zn and regulates Zn excretion from intestinal cells into the lumen of the gut, however, TTM-1A is not Zn regulated and its function remains unknown. 27 The RNAi bacteria we used here specifically targeted ttm-1a, but not ttm-1b. These results indicated a novel role of TTM-1A to transport Mn intracellularly.…”
Section: Functional Role Of C Elegans Homologs Of Human Slc30a10mentioning
confidence: 99%